2013
DOI: 10.1016/j.euromechsol.2012.10.008
|View full text |Cite
|
Sign up to set email alerts
|

On the two-dimensional solution of both adhesive and non-adhesive contact problems involving functionally graded materials

Abstract: This paper presents a semi-analytical algorithm for the determination of the contact half width and surface pressure which results from both adhesive and non-adhesive contact problems involving functionally graded materials (FGM). The inhomogeneously elastic solid comprises a graded elastic coating whose shear modulus depends exponentially on the vertical coordinate and a homogeneously elastic substrate. The solid is assumed to be in a state of plane strain and thus a two-dimensional analysis is performed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 25 publications
3
7
0
Order By: Relevance
“…The converse is true for the soft coating as an increase in coating thickness here leads to an decrease in the applied maximum pressure and an increase in the maximum surface deflection. These trends are in accord with the observations of Chidlow et al [31]. The sub-surface stress fields given in figure 9 correspond to the pressure curves presented in figures 8c and 8d.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The converse is true for the soft coating as an increase in coating thickness here leads to an decrease in the applied maximum pressure and an increase in the maximum surface deflection. These trends are in accord with the observations of Chidlow et al [31]. The sub-surface stress fields given in figure 9 correspond to the pressure curves presented in figures 8c and 8d.…”
Section: Resultssupporting
confidence: 81%
“…Johnson and Sridhar [30] also presented an adhesive model, based on the original JKR model, for a layered solid with a homogeneous elastic coating. Lately, Chidlow et al [31] investigated the e↵ects of surface adhesion between a rigid cylindrical indenter and a layered solid when in contact using Maugis's Dugdale model.…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that as the ratio h 1 /a h increases, the predicted contact half-width for the hard coating decreases yet the maximum pressure in the contact increases whilst the converse is true for a soft coating. This is an observation that has been made by other authors (e.g Teodorescu et al [5], Chidlow et al [6] and indicates that softer coatings are less likely to fail under pressure than harder coatings.…”
Section: Numerical Resultssupporting
confidence: 76%
“…The reader is referred to Chidlow et al [6] for the definition of the matrices appearing above and the remaining constants within the transition layer and substrate. We note however that the constants P n , n ∈ N are the coefficients in the Fourier series representation of the pressure and are defined as…”
Section: Methods Of Solutionmentioning
confidence: 99%
“…Sergici et al [19] applied a Maugis type adhesive model to investigate the contact between a spherical indenter and an elastic layered solid. More recently, Chidlow et al [20] and Chong and Chidlow [21] introduced surface adhesion via the Dugdale and Lennard-Jones potential respectively to simulate a rigid cylindrical geometry indenting a graded elastic layered solid comprising a FGM perfectly bonded to a homogeneous substrate.…”
Section: Introductionmentioning
confidence: 99%